AIDA DART asteroid deflection test: Planetary defense and science objectives. (August 2018) - Cheng, Andrew F.; Rivkin, Andrew S.; Michel, Patrick; Atchison, Justin; Barnouin, Olivier; Benner, Lance; Chabot, Nancy L.; Ernst, Carolyn; Fahnestock, Eugene G.; Kueppers, Michael; Pravec, Petr; Rainey, Emma; et al.
Abstract: The Asteroid Impact & Deflection Assessment (AIDA) mission is an international cooperation between NASA and ESA. NASA plans to provide the Double Asteroid Redirection Test (DART) mission which will perform a kinetic impactor experiment to demonstrate asteroid impact hazard mitigation. ESA proposes to provide the Hera mission which will rendezvous with the target to monitor the deflection, perform detailed characterizations, and measure the DART impact outcomes and momentum transfer efficiency. The primary goals of AIDA are (i) to demonstrate the kinetic impact technique on a potentially hazardous near-Earth asteroid and (ii) to measure and characterize the deflection caused by the impact. The AIDA target will be the binary asteroid (65803) Didymos, which is of spectral type Sq, with the deflection experiment to occur in October, 2022. The DART impact on the secondary member of the binary at ∼6 km/s changes the orbital speed and the binary orbit period, which can be measured by Earth-based observatories with telescope apertures as small as 1 m. The DART impact will in addition alter the orbital and rotational states of the Didymos binary, leading to excitation of eccentricity and libration that, if measured by Hera, can constrain internal structure of the target asteroid. Measurements of the DART crater diameter and morphology can constrain target properties like cohesion and porosity based on numerical simulations of the DART impact. Highlights: DART will be the first space mission to demonstrate asteroid deflection by kinetic impact. The DART impact on the moon of the binary asteroid Didymos will change the orbital period.